Предмет: Математика,
автор: ЗаЙko
5(2х - 3) - 2 (3 - 2х) = 15 - 6 ( х +1) ПОМОГИТЕ СРОЧНО КАК РЕШАТЬ
Ответы
Автор ответа:
0
5(2х - 3) - 2 (3 - 2х) = 15 - 6 ( х +1)
10х-15-6+4х=15-6х-6
14х-21=9-6х
14х+6х=9+21
20х=30
х=30:20
х=1.5
Автор ответа:
0
5(2х - 3) - 2 (3 - 2х) = 15 - 6 ( х +1)
10х-15-6+4х=15-6х-6
10х+4х+6х=15-6+15+6
20х=30
х=30/20
х=1,5
Похожие вопросы
Предмет: Қазақ тiлi,
автор: amina0089
Предмет: Другие предметы,
автор: gapanovich2704
Предмет: Қазақ тiлi,
автор: privet9036
Предмет: История,
автор: dzhugan2010